Profit Persistence: is There A Conglomerate Effect? The Case of Banking and Insurance in Morocco - Nabil Adel; Siham Meknassi (European Scientific Journal, ESJ, 2022)
This paper analyses profit persistence and its determinants in Morocco's banking and insurance sectors. The solid and increasing interdependencies between both actors are becoming a matter of concern for the regulatory authorities, as they threaten the country's financial stability. Using both static and dynamic hypotheses of the competitive environment model, we study the determinants of profit persistence in eight banks and eight insurance companies for 13 years, using a random-effects panel data model. While previous articles studied banks and insurers separately, we fill the gap in the literature by exploring the profit persistence as a result of their increasing capitalistic interdependence. Our results show a very low-profit persistence level, which signals a competitive financial sector. The main determinants of this profit persistence are diversification, efficiency, size, solvency, risk, and entry barriers. However, we find no evidence of any conglomerate effect, eliminating any synergy premium through cross participation between banks and insurance companies.